The Causes of Conflicts between Stakeholders and Educational Management - Chaudhary, Rajeshwer Prasad (International Research Journal of MMC, 2022)
The purpose of the article is to find out the causes of conflicts occurs in the colleges between the stakeholders and educational management by the help of different kinds of literature reviews. The study of article is based on the review of literature and the secondary data has been used. The causes of conflicts occur due to different kinds environment in the organization. That environment may be internal and external. The causes occur due to the misunderstanding, selfishness, dominating behaviour, insufficient resources, traditional planning ways, etc.